Perlindungan Hukum Terhadap Suatu Merek Terdaftar Di Indonesia - Manurung, Rachel Wahyunita Theodor; Silalahi, Wilma (LPPM STAI Muhammadiyah Probolinggo, 2025)
Trademarks, as intellectual works, must be respected and protected to safeguard the interests of individuals and groups. The concept of Intellectual Property Rights (IPR) is outlined as the result of human work that has economic value, and strong legal protection is required to encourage innovation and prevent rights violations. This research employs normative legal methods with secondary data sources, including statutory regulations, books, and scientific articles. The analysis is conducted through statutory approaches and content analysis methods.Law Number 20 of 2016 concerning Trademarks and Geographical Indications is identified as the legal foundation governing trademark rights, which are obtained through the